Flextime and sharing. - Meer, Jeff (Psychology Today, 1985)
A team of three management specialists has discovered that companies that offer their employees flexible work schedules may be able to anticipate an increase in production, particularly if employees had been sharing equipment. The team studied the productivity of computer programmers and keypunch operators in two Florida state government agencies, one of which had just instituted a flextime policy. The researchers found an increase in productivity among the computer programmers on a flextime schedule, but no appreciable difference in productivity among the keypunch operators, even if they were on a flextime schedule. The researchers theorize that the difference is due to the availability of the computer, which became more accessible to the programmers on flextime. The study was published in the Journal of Applied Psychology, Vol. 70, No. 2.